A review of vaccine research and development: Human acute respiratory infections() - Girard, Marc P. (Vaccine, 2005)
Worldwide, acute respiratory infections (ARIs) constitute the leading cause of acute illnesses, being responsible for nearly 4 million deaths every year, mostly in young children and infants in developing countries. The main infectious agents responsible for ARIs include influenza virus, respiratory syncytial virus (RSV), parainfluenza virus type 3 (PIV-3), Streptococcus pneumoniae and Haemophilus influenzae. While effective vaccines against influenza, H. influenzae type b (Hib) and S. pneumoniae infections have been available for several years, no vaccine is available at present against illnesses caused by RSV, PIV-3, metapneumovirus or any of the three novel coronaviruses. In addition, the threat constituted by the multiple outbreaks of avian influenza during the last few years is urgently calling for the development of new influenza vaccines with broader spectrum of efficacy, which could provide immunity against an avian influenza virus pandemic. This article reviews the state of the art in vaccine R&D against ARIs and attempts to address these basic public health questions.